1998
DOI: 10.1016/s0042-6989(97)00151-x
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of white light in photoreceptors

Abstract: The fraction F of incident light absorbed by a photoreceptor of length l has traditionally been given by F = 1 - e-kl, where k is the absorption coefficient of the photoreceptor. Unfortunately, this widely-used expression is incorrect for absorption of the type of light most common in natural scenes--broad spectrum "white" light--and significantly over-estimates absorption. This is because the measured values of k are only valid at the absorbance peak wavelength of rhodopsin, whereas at other wavelengths (whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
207
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(211 citation statements)
references
References 37 publications
3
207
0
1
Order By: Relevance
“…The peak sensitivity, however, was still too narrow, which may be due to the coloured screening pigments in the retinular cells. Our modelling did not include self-screening effects [38], because the exact numbers of each photoreceptor type contributing to the ant's closed rhabdoms are not yet known.…”
Section: Resultsmentioning
confidence: 99%
“…The peak sensitivity, however, was still too narrow, which may be due to the coloured screening pigments in the retinular cells. Our modelling did not include self-screening effects [38], because the exact numbers of each photoreceptor type contributing to the ant's closed rhabdoms are not yet known.…”
Section: Resultsmentioning
confidence: 99%
“…where k.A( ) is the absorption coefficient, k, multiplied by the relative absorbance (A) at wavelength λ and l = rhabdom length (Warrant &Nilsson, 1998). The absorbance values were obtained by fitting the template of Stavenga et al (1993) to the published values of k (proximal = 0.01 µm -1 , distal = 0.006 µm -1 ) and the peak absorbance wavelengths for the rhabdoms (proximal = 498 nm, distal = 410 nm) of Systellaspis debilis (Cronin & Frank, 1996).…”
Section: Methodsmentioning
confidence: 99%
“…In the present study the absorption coefficient for each wavelength has been calculated as shown in equation (1) above (Warrant & Nilsson, 1998). …”
Section: %; Hiller-adams Et Al 1988) This Is Because the Earliermentioning
confidence: 99%
“…Therefore, F is calculated for both light conditions. In white light, F w ϭ kl0~2.3 ϩ kl !, where k is the photoreceptor absorption coefficient (reported to be 0.035 mm Ϫ1 for teleosts, Land, 1981;Partridge, 1990;Warrant & Nilsson, 1998) and l is the outer segment length ( mm). For monochromatic light at the preferred wavelength of the photoreceptor, F l max ϭ 1 Ϫ e Ϫkl (Land, 1981;Warrant & McIntyre, 1990).…”
Section: S P Collin Et Almentioning
confidence: 99%
“…For monochromatic light at the preferred wavelength of the photoreceptor, F l max ϭ 1 Ϫ e Ϫkl (Land, 1981;Warrant & McIntyre, 1990). All calculations assume that the photoreceptors capture photons from an extended light source (Land, 1981;Warrant & Nilsson, 1998).…”
Section: S P Collin Et Almentioning
confidence: 99%